PENGARUH KOMITMEN ORGANISASI, KONFLIK PERAN, PROFESIONALISME, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK WILAYAH KOTA MEDAN) - Sitorus, Jessy Safitri; Boang Manalu, Ismail Hasan; Kosasih, Anggraina; Pasaribu, Swardin (Aksara Public, 2019)
This study discusses the influence of organizational commitment, Role Conflict, professionalism and leadership style against the performance of the Auditor. The scope of research is the public accountant who worked in the Office of Public Accountant. The purpose of this study was to analyze the influence of organizational commitment, Role Conflict, professionalism and leadership style against the performance of the Auditor. This research included in the quantitative research. The sample in this research as much as 7 Office of Public Accountant. This research data is primary data, where the data in this study were gathered using survey methods through the dissemination of the questionnaire directly to the respondents. Model analysis of this research in the form of multiple linear regression. The results showed that organizational commitment, professionalism and leadership styles of positive and significant effect on performance, while the auditor's role conflict and significant negative effect on performance of Auditors.